'Diversion or safety net?' Institutions and public opinion on vocational education and training. (October 2017) - Di Stasio, Valentina
Vocational education and training (VET) has been described in the sociological literature as a mixed blessing. On one hand, vocational qualifications facilitate the school-to-work transitions of youth (safety net function of VET); on the other hand, placement into vocational tracks dissuades students from attending higher education (diversion function of VET). In this study, I analyse whether VET is perceived to function as a safety net and/or a diversion route by the public at large. VET systems greatly vary across countries with regard to their perceived prestige, the involvement of social partners in the provision of training and the certification of occupational skills. Thus, I focus on whether perceptions of VET vary systematically across countries. Using Eurobarometer data from 2011, I show that in countries with occupationally oriented VET systems, which provide work-based training in the form of apprenticeships, both the safety net and diversion functions are recognized as distinctive aspects of VET. Although public perceptions of the safety net function do not vary across education groups, the analyses show that highly educated individuals are less likely than the other education groups to suggest vocational education as an option, even when they do recognize its role as a safety net. This study contributes to our understanding of the micro-level mechanisms that underlie the formation of educational preferences across social groups.